Pemberdayaan Penyandang Disabilitas melalui Literasi Keuangan Digital untuk Meningkatkan Resiliensi Keuangan di Yogyakarta - Ratna Candra Sari; Annisa Ratna Sari; Dian Juliani; Novita Nurbaiti; Arsy Widiyanti; Dian Normalitasari Purnama (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
People with disabilities have gaps in access to conventional and digital financial services, and have credit limitations. Therefore, financial literacy assistance is needed to form financial resilience for people with disabilities. This service was carried out in the form of digital financial literacy assistance for people with disabilities for ULD UGM's fostered partners, namely the Indonesian Women with Disabilities Association (HWDI) Sleman. The service aims to increase the contribution of universities in digital financial literacy education for people with disabilities, as well as build financial resilience for people with disabilities through digital financial literacy for the ULD UGM fostered partners. The PkM activity will be held offline on July 3, 2025 at Kopi Candi Pakem, Sleman. In addition, online assistance was carried out with the HWDI Sleman coordinator. The outputs resulting from this service are (1) Certificates from partners that explain the lecturer as resource persons and facilitators during the activity, (2) Cooperation Manuscripts/IA, (3) Social media publications, (4) Posters, and (5) Intellectual Property Rights. The results of this PkM activity are: 1) Participants gain knowledge and insight into accounting literacy (financial recording), digital financial literacy, and marketing strategies for entrepreneurs; 2) Participants play an active role in the implementation of service activities; 3) Most of the participants considered that the service activities were carried out very well.